DUKUNGAN KELUARGA DENGAN FREKUENSI KEKAMBUHAN PASIEN HALUSINASI PENDENGARAN DI RUMAH SAKIT JIWA MENUR SURABAYA - Chindy Maria Orizani; Yohanes Kurniawan (STIKes Adi Husada, 2018)
ABSTRACT Hallucinatory hearing is a mental disorder that can experience relapse, one of the things to reduce the recurrence of auditory hallucinations is the role of the family when handling the patient at home. This study aims to analize the relationship between family support with the frequency of auditory hallucinations recurrence in RSJ Menur Surabaya. In this research used correlation research design with cross sectional approach. The population was family which had hallucinations patient. The sampling used purposive sampling technique. The dependent variable in this research was family support and dependent variable was frequency of recurrence. Instrument used in data collection were questionnaire and demographic data sheet. After the research, the results of this study there was not a relationship of family support with the frequency of auditory hallucination recurrence in RSJ Menur Surabaya. Test results spearman rank test p= 0,085 which mean p> α 0,05. The highest value of family support was quite as much 18 response (45%) and the highest frequency of recurrence of hallucination patient was moderate as much 16 response (40%). The conclusions of this study were no association between family support and the frequency of recurrence of auditory hallucinations in RSJ Menur Surabaya. Suggestions to future develop the sciences and use questionnaires that have been tested for validity for more accurate resuits. Keyword : family support, recurrence, auditory hallucinations